Seasonal methane emissions and agronomic performance of Indonesia’s high-yielding rice cultivars on the north coastal rice fields of Central Java, Indonesia - Rina Kartikawati; Budiastuti Kurniasih; Eka Tarwaca Susila Putra; Eko Hanudin; Noppol Arunrat (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2024)
Rice contributes significantly to methane emissions. In the north coastal region of Central Java Island, flooding irrigation for high-yielding rice cultivation is used throughout the rice-producing season to reduce the salinity effect. Information on methane emissions in coastal rice fields, particularly in salt-affected soil, is still limited. This study aimed to measure the methane emissions from different high-yielding rice varieties and examine the association with agronomic performance. The study site was in the Wedung district of Demak Regency, Central Java, and the research was carried out from November 2022 to March 2023. Eight rice cultivars—Ciherang, Inpari 32, Inpari 34, Inpari 35, Biosalin 1, Biosalin 2, Inpari Unsoed 79, and Inpari 30—were investigated. The experiment was designed as a randomized block with four replications. Methane gas samples were collected during the growing season in relation to rice stages. There were substantial differences in methane emissions among the eight rice varieties. Inpari 32, Ciherang, and Biosalin 1 had higher rice yields and lower yield-scale methane emissions than the other five rice varieties. Grain production and effective tiller number were significantly (p<0.01) and inversely linked to methane emissions. We found Inpari 32, Ciherang, and Biosalin 1 to be low-methane and high-yielding rice cultivars in salt-affected soil. These findings suggest that the use of these rice varieties by coastal farmers could help mitigate greenhouse gas emissions.